Multimodal Analgesia With Long-Acting Dinalbuphine Sebacate Plus Transversus Abdominis Plane Block for Perioperative Pain Management in Bariatric Surgery: A Case Report - Liu, Shih-Yuan; Ho, Yi-Hong; Wong, Chih-Shung (Frontiers in Pharmacology, 2021)
Laparoscopic bariatric surgery is increasingly performed in morbidly obese patients. However, post-surgical pain is common and is usually managed with classical opioids such as morphine and fentanyl. Further, morbidly obese patients are predisposed to opioid-related side effects, especially post-operative nausea and vomiting (PONV) and respiratory depression. Obstructive sleep apnea in morbidly obese patients even predisposes them to respiratory depression. Thus, reducing opioid consumption is important. Multimodal analgesia (MMA) provides optimal perioperative analgesia while minimizing opioid consumption. Studies showed that MMA strategy provides satisfying pain relief in bariatric surgery with enhanced recovery. There are very few reports on the use of dinalbuphine sebacate (DS), a newly introduced non-controlled distinguishing opioid medication with long-lasting analgesic effects. DS has a different mechanism of action from that of morphine or fentanyl and is non-addictive, with minimal side effects. It has been successfully used in laparoscopic cholecystectomy in our previous study. We, in this case report, conducted a new MMA protocol with DS on a 46-year-old morbidly obese female patient who underwent laparoscopic sleeve gastrectomy. The MMA protocol included ultrasound-guided intramuscular DS injection plus transversus abdominis plane (TAP) block and other analgesics; it achieved good perioperative analgesia with opioid-sparing effect and enhanced patient’s recovery with no pain in the following 4 months.